Sildenafil promotes osteogenic differentiation of human mesenchymal stem cells and inhibits bone loss by affecting the TGF-β signaling pathway - Menglong Hu; Likun Wu; Erfan Wei; Xingtong Pan; Qiyue Zhu; Xv Xiuyun; Letian Lv; Xinyi Dong; Hao Liu; Yunsong Liu (Stem Cell Research & Therapy)
Abstract Background Osteoporosis, a common bone disorder, is primarily managed pharmacologically. However, existing medications are associated with non-trivial side-effects. Sildenafil, which already finds many clinical applications, promotes angiogenesis and cellular differentiation. Osteoporotic patients often exhibit a reduced intraosseous vasculature and impaired cellular differentiation; sildenafil may thus usefully treat osteoporosis. Methods Here, the effects of sildenafil on the osteogenic differentiation of human mesenchymal stem cells (hMSCs) were explored, as were the molecular mechanisms in play. We treated hMSCs with varying concentrations of sildenafil and measured cell proliferation and osteogenic differentiation in vitro. We used a mouse model of subcutaneous ectopic osteogenesis to assess sildenafil’s effect on hMSC osteogenic differentiation in vivo. We also explored the effects of sildenafil on bone loss in tail-suspended (TS) and ovariectomized (OVX) mice. Mechanistically, we employed RNA-sequencing to define potentially relevant molecular pathways. Results The appropriate concentrations of sildenafil significantly enhanced osteogenic hMSC differentiation; the optimal sildenafil concentration may be 10 mg/L. Sildenafil mitigated osteoporosis in OVX and TS mice. The appropriate concentrations of sildenafil probably promoted hMSC osteogenic differentiation by acting on the transforming growth factor-β (TGF-β) signaling pathway. Conclusions In conclusion, sildenafil enhanced hMSC osteogenic differentiation and inhibited bone loss. Sildenafil may usefully treat osteoporosis. Our findings offer new insights into the physiological effects of the medicine. Graphical Abstract